Ukrainian music with a jewish accent: «Six jewish melodies» by Yuri Ishchenko and «Carpe diem» by Oleg Bezborodko - Solomonova, Olga (Scientific herald of Tchaikovsky National Music Academy of Ukraine, 2024)
The relevance of the study. The Jewish theme is quite a popular idea of world art. Its powerful panorama in Ukraine is unfolded by musical works dedicated to the unprecedented Holocaust of the Jews of Kiev in Babi Yar. Meanwhile, the Jewish discourse of Ukrainian music is not limited to this content. The need to study new versions of the reproduction of Jewish intonation in “Six Jewish Melodies” by Yuri Ishchenko and in “Carpe diem” by Oleg Bezborodko Ukrainian composers ensures the relevance of the article. The main objective of the study to present a musicological analysis of the works "Six Jewish Melodies" by Yu. Ishchenko and "Carpe diem" by O. Bezborodkо, which represent contrasting versions of the Jewish discourse of Ukrainian academic music of the 21st century. The methodology includes the following research methods: source studies - in the process of finding out folklore sources of the cycle "Six Jewish Melodies" by Y. Ishchenko; hermeneutic-semantic and intonation-dramaturgical methods, which made it possible to reveal the figurative and intonation specificity of the works; and comparative method with a two-level analytical comparison of a) the quoted material with its composer’s version; b) two works studied in the article. Results and conclusions. «Six Jewish Melodies» by Yu. Ishchenko and «Carpe diem» by O. Bezborodko are analyzed - two polar versions of Jewish discourse that demonstrate the dynamic and multivariate history of the entry of Jewish intonation into academic Ukrainian music of the ХХІ century. The main idea of «Six Jewish Melodies» is the preservation of the intonational and figurative resources of Jewish authenticity, emphasizing its intristical lamentable semantics. The style of the work, despite the genre diversity (chant without words, lyrical song, lullaby, freylekhs) is monolexical, based on the reproduction of “pure” Jewish intonation. An absolute contrast to the above is a playful fantasy «Carpe Diem»: the Jewish melodies «Roast Chicken» and «Seven-Forty» are grotesquely synthesized with themes of Fate and «Ode to Joy» by Beethoven. Such a hybrid substance based on a disjunctive synthesis of thematic counterparts, reveals globalistic tendencies and wrings to cocoon different time-spatial, genre-style and national-mental characteristics. The style of this piece is polylexical, intensely dialogical, inverting the entire hierarchy of upper and lower cultural coordinates. Each of the works analyzed adapts different genre content of Jewish music. Yu. Ishchenko quotes unfamiliar melodies from the sphere of archaic folklore genres. On the contrary O. Bezborodko, turns to the well-known Jewish melodies of the «low» urban tradition, which are paradoxically synthesized with the «high» themes of Beethoven. The desacralization of Beethoven’s cult themes, which reveal «consanguinity» with Odessa-Jewish musical content, symbolizes the process of «initiation into the Jews» of the great composer. These pieces of work also have something in common. In addition to convergence on the mental level - through the reproduction of an antithetical picture of the Jewish worldview, the manifestation of the author’s empathy and reliance on quotes, this is the presence, along with the authors, of intertextual co-authors. In «Six Jewish Melodies» this is the researcher of Jewish folklore Moses Beregovsky, in «Carpe diem» - Ludwig van Beethoven; their personalization occurs through the introduction of musical citations. The different intonation concepts of these two musical works seemed to unite into integral whole different projections of the universal-syncresive Jewish mentality, devoid of figurative autonomy, which combines primordial melancholy and a positively humorous worldview. The study of new implementations of the Jewish discourse of modern Ukrainian music, along with identifying the specifics of the piano version of «Carpe diem» by О. Bezborodko, constitutes perspectives for the follow up studies.